Impact of stress and coping strategies on quality of life in hematological malignancies: A cross-sectional study - Yue Qi; Kangsheng Zhu; Wei Liu; Xiaolei Xu (PLoS ONE, 2025)
Background and aims While perceived stress and coping strategies have been established as significant determinants of quality of life (QoL) in patients with solid malignancies, their impact on hematological malignancy population have not been fully elucidated. This study aimed to examine how perceived stress and medical coping strategies interact with sociodemographic factors to influence QoL in patients with hematologic malignancies. Methods The study, involving 185 hematologic cancer patients in China, was conducted between August 2024 and December 2024. Self-reported scales were used to assess QoL, perceived stress and medical coping strategies. Data analysis included univariate analyses, Pearson correlation, and multivariate regression analyses using SPSS V26.0. Results 178 patients completed the survey with a response rate of 96.2%. The overall QoL score was 55.99 ± 24.6 indicating a moderate-to-low level. The functional domains averaged 64.81 ± 21.83, while the symptomatic domains averaged 24.95 ± 19.38. The overall QoL was associated with age, sex, marital status, place of residence, type of insurance (p < 0.05). Stress perception (r = −0.389, −0.591), crisis perception (r = −0.489, −0.638), and yielding coping (r = −0.479, −0.547) exhibited significant negative correlations with overall QoL and functional scores, respectively (p < 0.001). Stress perception (r = 0.435), crisis perception (r = 0.535), avoidance (r = 0.280), and yielding (r = 0.472) were positively correlated with symptom scores (p < 0.001). Multiple linear regression analysis identified sex, crisis perception, and yielding as key factors affecting overall QoL (explaining 36.5% of the variance) and functional status (explaining 45.6% of the variance), while residence, crisis perception, avoidance, and yielding significantly influenced the symptomatic fields (34.2% variance) in patients with hematological malignancies (p < 0.05). Conclusions This study revealed that the QoL of patients with hematological malignancies is generally suboptimal and influenced by sex, crisis perception, and stress-coping strategies. These findings underscore the need for integrated psychosocial interventions targeting stress management and adaptive coping strategies in clinical care. This study contributes to the growing body of evidence on psychosocial determinants of QoL in oncology and can inform tailored supportive care programs for this population.